UPACARA MENEK DEHA - Widyawati, Anak Agung Ayu Alit; Ambarnuari, Mery (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
The Humans in their lives will pass the stages of growth and development. Hinduism has ceremonies that must be passed in entering the stages of human life. One of them is a ceremony given to children who reach adolescence which is marked by menstruation in girls and nocturnal orgasm and the voice become deep in men. The ceremony that is given to children who are teenagers is called the menek deha ceremony. The procession is start with take a bath, shampooing, and then matur piuning, melukat or majaya-jaya ritual, mabyakala and maprayascita ritual, natab sesayut rah and sesayut ngraja singa ritual, marriage with Sang Hyang Semara Ratih ritual, pray to the family temple, pengekeban ritual, mapadamel ritual, and the last is pengliwetan ritual. This ceremony are using banten such as: pejati, byakala, prayascita, duurmenggala, bayuan, suci, ayaban tumpeng pitu, sayut pengambiyan, sesayut sabuh rah, sesayut ngeraja singa, padedarian, and canang lengawangi-buratwangi. This ceremony is part of the Manusa YajÅ„a ceremony which aims to obtain purification, salvation, and an increase in status both physically and mentally.